Vintage Ladies in Cubist Exhibitions: Pablo Picasso's Cubist Women and Judith Butler's Performativity - Samaneh Saeid; Laleh Atashi (k@ta: A Biannual Publication on the Study of Languange and Literature, 2020)
As a prominent figure in the history of painting, Pablo Picasso has bestowed upon the world his uniquely striking paintings in different styles, the most revolutionary of which being his Cubist art. The representation of women occupies a significant space in Picasso’s Cubist works. While the painter’s style is highly revolutionary, rejecting the accepted principles of painting, the subject matter does not change as such: nude women are objectified with a cubist look. Judith Butler’s theory of gender performativity which examines the roots of naturalized concepts of gender, has been applied to Picasso’s representations of women in his cubist paintings. This research examines the way naturalized definitions of gender have found their way into Picasso’s paintings. By applying the Butlerian concept of gender performativity to a number of Picasso’s cubist artworks, we try to indicate how stereotypes of gender linger in the discourse of modernism. Analyses lead to the conclusion that although the cubist style of painting is an experimentation in form, hardly any avant-gardism can be traced in the representation of gendered identities in Picasso.